Electroosmotic reinforcement mechanism and laboratory tests of pulsating direct current with a high energy efficiency ratio - Xunli Zhang; Lingwei Zheng; Shangqi Ge; Xudong Zheng; Xinyu Xie (Soils and Foundations, 2024)
Based on the electroosmotic reinforcement mechanism of pulsating direct current (PDC) with a high energy efficiency ratio, the calculation method of PDC electroosmosis drainage rate was verified under different potential gradients using two forms of voltage loading, i.e., constant direct current (CDC) and PDC. The drainage weight and electric current were achieved by laboratory tests, and then the energy efficiency ratio, soil resistivity and contact resistance was calculated. The energy consumption of each test group was analyzed by considering the initial potential gradient. The obtained results show that under the same potential gradient, the difference in soil resistivity and electroosmotic drainage between PDC and CDC is not significant, but there is a significant difference in contact resistance, which leads to low current intensity and high energy efficiency ratio in the PDC test group. The expression of the electroosmotic drainage rate of the PDC is described with the coefficient μ, and then the energy efficiency ratio versus potential gradient curve is calculated, which is in good agreement with the experimental results. The reason for the lower energy consumption of PDC electroosmosis compared to CDC is described in terms of the drainage mechanism of electroosmosis.